Job involvement and organizational burnout: a gender-sensitive approach in social work - Cădariu, Ioana-Eva; Rad, Dana (Technium Social Sciences Journal, 2025)
This study examined gender-specific predictors of job involvement among social workers by investigating the roles of burnout dimensions, perceived organizational support, and professional experience. A total of 138 participants (66.7% women, 33.3% men) completed validated self-report measures, including the Job Involvement Questionnaire, the Maslach Burnout Inventory–General Survey, and the Perceived Organizational Support Scale. Separate multiple regression analyses were conducted by gender. Results indicated that emotional exhaustion significantly and negatively predicted job involvement among men (β = –.57, p = .001), whereas experience (β = .45, p < .001) and cynicism (β = .29, p = .042) were significant positive predictors for women. Perceived organizational support and professional inefficacy were not significant predictors in either group. These findings highlight the necessity of gender-sensitive approaches in organizational interventions aimed at sustaining professional engagement in the social work sector.